INFLUENCE OF CURBSIDE PUBLIC FACILITIES ON PASSENGER COMFORT AT RADIN INTEN II INTERNATIONAL AIRPORT, INDONESIA: A Quantitative Study of Public Infrastructure Impact on Airport Service Quality - TARUKAN, I MADE DENNY; Hartono, Hartono; Rozi, Fahrur (Journal of Public Transportation Community, 2025)
This study examines the influence of curbside facility services on passenger comfort at Radin Inten II International Airport, Lampung. Using a quantitative approach with 44 respondents, the study applied Spearman’s Rank correlation and simple linear regression. Results indicate that all six facilities significantly affect passenger comfort, with charging stations showing the strongest influence (β = 0.852; ρ = 0.841) and lactation rooms the weakest (β = 0.399; ρ = 0.373). The findings suggest that improving curbside infrastructure in accordance with national standards is essential for enhancing passenger satisfaction.